Peningkatan Pengetahuan Tentang Kebersihan Alat Genetalia Eksterna Selama Menstruasi Pada Remaja Putri - Bimayanti, Lutfiana Eka; Haniyah, Siti; Ningrum, Ema Wahyu (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Adolescent girls are a vulnerable group to reproductive health problems, particularly during menstruation, such as vulvar pruritus and vaginal discharge. A pre-survey at the Mayasari Posyandu revealed that most adolescents had limited understanding of external genital anatomy, were not accustomed to changing sanitary pads regularly, and experienced itching without knowing the causes or preventive measures. This condition reflects the lack of education regarding vulvar hygiene during menstruation. This Community Service activity was carried out to improve adolescent girls’ knowledge about external genital hygiene during menstruation. The methods included a pre-survey, pre-test, educational sessions through lectures, discussions, animated videos, and pocketbooks, followed by a post-test and follow-up monitoring. The activity was conducted in two sessions involving 35 respondents. The results showed a significant increase in knowledge, from the initial condition where the majority of respondents were in the moderate category (51%) with an average pre-test score of 63.4, to the majority being in the good category (86%) with an average post-test score of 84.7 after being given education related to the hygiene of the external genitalia during menstruation. These findings demonstrate that interactive health education methods are effective in enhancing adolescents’ understanding of the importance of maintaining external genital hygiene during menstruation. This activity is expected to have a positive impact in reducing the risk of infection and increasing adolescent girls’ awareness of reproductive health